Docentes investigadores: superar los sentidos metafóricos que viajan del norte al sur global - Cuineme-Rodríguez, Mónica Yasmín; Castiblanco-Roldán, Andrés (Educación y Ciudad, 2023)
This reflection is based on a systematic process of documentary review of both theoretical texts referring to the subject, as well as systematization documents that to a certain extent account for its application in educational settings. We will use metaphor in its power as a key analysis term in symbolic interaction. Fruit of philosophy and discursive analysis, we will play in a critical key using as a mechanism of analysis the possibility of tension that has the metaphorical sense as part of rhetoric and therefore of discourse, in terms of Paul Ricoeur (2001). With this reflexive tool, in this text we will deal with presenting two tensions: first, we locate what it represents in the condition of basic and secondary education teachers to assume or identify themselves as research teachers before a scientific and exclusive academy. As a second, we propose a tension with reference to the counter-hegemonic discourses of civilizational forms in which educational research is assumed as a process of resistance and therefore the role of the research teacher is involved within the discourse of social transformer in which, As happens in the scientific field, there is a discursive trap, which affects the assimilation of the production of meaning of the research teacher, in the great ideological course of other pedagogies, losing its independence as a situated intellectual production.